Socialization Of Religious Tourism Development As An Effort To Preserve Local Spiritual And Cultural Values In Batam City - Dailami; Moh. Thandzir; Rezki Alhamdi; Natal Olotua Sipayung; Syafruddin Rais; Wahyudi Ilham; Haufi Sukmamedian; Syailendra Reza Irwansyah Rezeki; Gita Irmalya (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
The Community Service Activity (PKM) with the title